TAP-Stenting Technique for Bifurcation Stenosis of Celiac Artery - Yucel Colkesen; Taner Seker; Osman Kuloglu; Murat Çayli (Case Reports in Vascular Medicine)
We report a clinical course of a patient who developed severe ischemic liver injury and total occlusion of the celiac artery (CA). A 40-year-old man presented with abdominal pain. Computed tomography indicated total occlusion of the CA. Laboratory data demonstrated markedly elevated hepatic enzymes. An exploratory laparotomy was not necessitated due to absence of peritonism. The patient was successfully treated by endovascular recanalization of the CA occlusion via transcatheter balloon angioplasty and TAP-stenting (T-stenting and small protrusion) technique. Endovascular intervention in patients solely with liver failure appears practicable and early treatment is advised.